Serological survey and associated risk factors of Aujeszky’s disease virus in wild boar from south and central Poland - Didkowska Anna; Klich Daniel; Matusik Katarzyna; Kwiecień Ewelina; Tchórz Wiktoria; Welz Mirosław; Skibniewski Bartosz; Kwieciński Piotr; Mierkiewicz Michał; Anusz Krzysztof (Journal of Veterinary Research, 2025)
Aujeszky’s disease is caused by suid herpesvirus-1, also called Aujeszky’s disease virus (ADV). The main reservoir host is the wild boar (Sus scrofa). The last data about ADV seroprevalence in wild boar in Poland came from over 10 years ago. There is a gap in knowledge about the current epidemiological situation. Therefore, this study aimed to characterise ADV seroprevalence and risk factors in hunted wild boar in south and central Poland.